2018
DOI: 10.1039/c7ee03062b
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ni content on the thermoelectric properties of half-Heusler TiNiSn

Abstract: Thermoelectric properties vary dramatically between two boundary compositions of Ni-rich and Ni-poor TiNiSn, up to 25% in zT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 34 publications
6
91
0
Order By: Relevance
“…The magnitude of ρ follows the Ni 4d site occupancy and reduces from 9 mΩ cm (Ni 4d = 0.019) to 2 mΩ cm (Ni 4d = 0.08). S 2 /ρ increases from 0.5–1 mW m −1 K −2 at 313 K to maximum values of 2.5–3 mW m −1 K −2 at 550–700 K. These values are comparable to other literature reports [ 16 , 19 , 25 ], although in some studies larger S 2 /ρ ≥ 4 mW m −1 K −2 have been reported [ 18 , 35 ]. The y = 0.25 sample contains 26 wt % metallic FH phase and this sample should be considered a composite of HH (Ni 4d = 0.09) and FH phases.…”
Section: Resultssupporting
confidence: 88%
“…The magnitude of ρ follows the Ni 4d site occupancy and reduces from 9 mΩ cm (Ni 4d = 0.019) to 2 mΩ cm (Ni 4d = 0.08). S 2 /ρ increases from 0.5–1 mW m −1 K −2 at 313 K to maximum values of 2.5–3 mW m −1 K −2 at 550–700 K. These values are comparable to other literature reports [ 16 , 19 , 25 ], although in some studies larger S 2 /ρ ≥ 4 mW m −1 K −2 have been reported [ 18 , 35 ]. The y = 0.25 sample contains 26 wt % metallic FH phase and this sample should be considered a composite of HH (Ni 4d = 0.09) and FH phases.…”
Section: Resultssupporting
confidence: 88%
“…60 For our samples, the alloy scattering most likely originates from the X-site, as there is no evidence for the presence of substantial amounts of interstitial Ni from the NPD analysis (Table S1 †). Recent literature has conrmed the suppression of the electron mobility by interstitial Ni, 46,62,63 and our results on interstitial Cu are therefore highly relevant as they afford the possibility of increased phonon scattering without detriment to the electrical transport. This very different impact is supported by our DFT calculations that show the presence of in-gap states for interstitial Ni, which provide a possible route for carrier scattering, while these are absent in the Cu case.…”
Section: Single Parabolic Band Modellingmentioning
confidence: 59%
“…However, it is difficult to determine the excess amount of interstitial B atoms since there is a controversial solid solubility limit of B in the vacant position [20][21][22][23][24]. Recently, a convincing study on the solid solubility of Ni in the vacant position of TiNi 1+x Sn half-Heusler has been conducted by using the phase diagram technique [25]. The narrow temperature-dependent solubility range (e.g., 0 ≤ x ≤ 0:06 at 1223 K in TiNi 1+x Sn) was observed through phase boundary mapping on a Ti-Ni-Sn phase diagram.…”
Section: Introductionmentioning
confidence: 99%